Marbles and bullets [videorecording (DVD)] - Witt, Richard De; Hensley, Shuler; Palmer, Christopher-Lawson; Shipe, Kelly (Glass House Distribution, 2024)
Confederate soldier Samuel Barnett and a group of soldiers are on the battlefield. Samuel spots Jeremiah, a ten-year-old slave boy wandering through the woods right into the killing zone. As the battle erupts, Samuel makes the fateful decision to charge through the hell-fire and saves Jeremiah from the wrath of war. Coming face-to-face with death, Samuel soon starts to question his war torn life, Confederate philosophies, and the meaning behind his instincts to save a black child's life.